Bayesian rank-based hypothesis testing for the rank sum test, the signed rank test, and Spearman's ρ. Issue 16 (9th December 2020) - van Doorn, J.; Ly, A.; Marsman, M.; Wagenmakers, E.-J.
Abstract : Bayesian inference for rank-order problems is frustrated by the absence of an explicit likelihood function. This hurdle can be overcome by assuming a latent normal representation that is consistent with the ordinal information in the data: the observed ranks are conceptualized as an impoverished reflection of an underlying continuous scale, and inference concerns the parameters that govern the latent representation. We apply this generic data-augmentation method to obtain Bayes factors for three popular rank-based tests: the rank sum test, the signed rank test, and Spearman's ρ s .